Safety and immunogenicity of an mRNA-1273 vaccine booster in adolescents - Amparo L. Figueroa; Kashif Ali; Gary Berman; Wenqin Xu; Weiping Deng; Bethany Girard; Anne Yeakey; Karen Slobod; Jacqueline Miller; Rituparna Das; Frances Priddy (Human Vaccines & Immunotherapeutics)
Safety, immunogenicity, and effectiveness of an mRNA-1273 50-μg booster were evaluated in adolescents (12–17 years), with and without pre-booster SARS-CoV-2 infection. Participants who had received the 2-dose mRNA-1273 100-µg primary series in the TeenCOVE trial (NCT04649151) were offered the mRNA-1273 50-μg booster. Primary objectives included safety and inference of effectiveness by establishing noninferiority of neutralizing antibody (nAb) responses after the booster compared with the nAb post-primary series of mRNA-1273 among young adults in COVE (NCT04470427). Binding antibody (bAb) responses against SARS-CoV-2 variants of interest and COVID-19 incidence after vaccination were also evaluated. Median boosting interval was 315 days. The mRNA-1273 booster was well-tolerated, with an acceptable safety profile. Relative to pre-booster, nAb geometric mean levels increased after the booster by 17.8-fold and 4.7-fold among pre-booster SARS-CoV-2–negative and –positive participants, respectively. Effectiveness was successfully inferred based on noninferiority of nAb levels from mRNA-1273 booster dose (Day 29) compared with nAb levels after mRNA-1273 primary series (Day 57) among young adults in COVE. Further, the booster increased bAb levels relative to pre-booster baseline against SARS-CoV-2 variants (alpha [B.1.1.7], beta [B.1.351], gamma [P.1], and delta [B.1.617.2]), regardless of pre-booster SARS-CoV-2 status. COVID-19 incidence (cases per 1000 person-months) was lower among boosted (0 cases) than non-boosted (95.766 cases) participants in January 2022, a peak period during the early omicron transmission. In summary, the mRNA-1273 50-μg booster induced robust nAb responses in previously vaccinated adolescents, regardless of SARS-CoV-2 serostatus. Effectiveness was successfully inferred and the booster was well-tolerated, with no new safety concerns identified.